2021
DOI: 10.1111/ans.16469
|View full text |Cite
|
Sign up to set email alerts
|

The prescription of best medical therapy following infrainguinal bypass grafting in Australia and New Zealand: a multicentre Australasian audit

Abstract: This article is an audit across five hospitals in Australia and New Zealand of 688 infrainguinal bypass operations, looking at which patients were discharged on appropriate medical therapy post‐operatively. It highlights a large gap in clinical care across Australia and New Zealand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 25 publications
(48 reference statements)
2
9
0
Order By: Relevance
“…A recent ANZ study suggested that 460/688 (66.9%) patients that underwent infrainguinal bypass were prescribed an antihypertensive, lipid-lowering and antithrombotic medication. 14 This was similar to our study (62%) and highlights the under-prescribing of cardioprotective medications.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…A recent ANZ study suggested that 460/688 (66.9%) patients that underwent infrainguinal bypass were prescribed an antihypertensive, lipid-lowering and antithrombotic medication. 14 This was similar to our study (62%) and highlights the under-prescribing of cardioprotective medications.…”
Section: Discussionsupporting
confidence: 91%
“…The decision to start lipid‐lowering medication is based on individual CVD risk, not cholesterol levels 19 . Despite this, lipid‐lowering medications was the most omitted medication, similar to other studies 14 . Furthermore, younger patients experienced a larger gap, with only 70% of the PAD population aged 40–49 years covered.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…In another study, patients with PAD included in a guidelines-based risk reduction education program, which promoted overall control of cardiovascular risk factors and the use of drugs with demonstrated cardiovascular benefit, including statins, had a reduction in cardiovascular and lower extremity events at seven years of follow-up ( 176 ). However, the prescribing of these cardioprotective drugs remains insufficient and one-third of patients undergoing surgical revascularization do not receive them ( 177 ).…”
Section: Statin Prescription Rate In Patients With Peripheral Arterial Diseasementioning
confidence: 99%